ONLINE SKILLS FOR 21ST CENTURY TEACHERS: ESSENTIAL COMPETENCIES FOR MODERN EDUCATION - Karimova Nozima Alisher qizi; Nabiyeva Khilola (Web of Journals Publishing, 2024)
This article explores the essential online skills required by 21st-century teachers to effectively engage and educate students in a digital learning environment. It delves into the various digital competencies, such as proficiency with educational technology, online communication skills, and digital content creation. The article provides an overview of the critical skills needed, discusses relevant research, outlines the research methodology, presents key findings, and concludes with practical implications for professional development and continuous learning for educators. By examining the evolving role of teachers in a digital age, this article highlights the importance of continuous professional development and adaptation to new technologies to enhance teaching efficacy and student learning outcomes.